Measuring Social Preferences in Developing Economies - Vojtěch Bartoš; Ian Levely (Center for Economic Studies and ifo Institute (CESifo), 2023)
For the past two decades, studies measuring social preferences in developing settings have played an important role in building our understanding of economic development and poverty. This book chapter reviews lab-in-the-field experiments that measure social preferences, summarizes categories of social preferences, the standard experimental games that have been developed to test them, and why they are of interest to development economists. We describe experimental methodology adapted for developing contexts, give an overview of some recent advances in measuring social preferences in developing settings, we comment on the external validity of standard experimental games, and discuss unincentivized measures of social preferences. Finally, we review studies that explain variations in social preferences between and within individuals, with a focus on environmental factors. We comment on possible paths forward.
Keywords: A33; B41; C90; D90; O12; 330; social preferences; development economics; measurement; experimental methodology